Tax Regime in Nepal-Implications on Human Rights - Omwesiga, Dagan (Kathmandu School of Law Review, 2018)
This paper examines how tax abuse affects the realization of human rights in Nepal. Nepal is losing approximately 597 million US dollars through tax evasion and other illicit financial flows annually; it is no surprise that over 25.2 percent of the population lives below the national poverty line. This shows that they lack access to basic human rights such as the right to food, the right to housing, the right to clothing and above all, the right to health. This article explores how human rights in Nepal have evolved over time and how they are protected along with the available remedies through national and international mechanisms. Additionally, it examines the available mechanisms and remedies for the breach of human rights. To contextualize the concept offered, this write-up explores the research produced by scholars and the steps that have been taken by organizations like United Nations and the International Bar Association to establish a link between illicit financial flows and violation of human rights. In conclusion, the paper provides some recommendations to both the government of Nepal and business enterprises.